التطبيقات الدعوية للمقاصد الضرورية لحفظ العقل من خلال السيرة النبوية: دراسة تحليلية: The Da‘wah Applications of the Essential Objectives for Preserving the Intellect Through the Sīrah of the Prophet Muhammad (Peace be upon him): An Analytical Study - رشيد أحمد (الدراسات الإسلامية, 2024)
This study examines the da‘wah applications of the fundamental Islamic objective of preserving the intellect, as derived from the Prophetic biography (Sīrah). It underscores the centrality of intellect in Islamic jurisprudence. Through an analysis of Qura’nic verses, Prophetic traditions, and historical sources, the study delineates the methodologies employed to safeguard the intellect, including promoting education, prohibiting intoxicants, and adopting thoughtful dialogue. Specific applications encompass the prohibition of harmful substances, intellectual development through teaching, and fostering critical thinking through reflections on past nations and natural phenomena. The study underscores practical methodologies for both preachers and audiences, emphasizing the significance of rational and ethical frameworks in the practice of Ba‘wah. These methodologies encompass the use of evidence-based reasoning, addressing misconceptions, and engaging in constructive dialogues. By analysing these strategies, this study highlights the critical role of preserving intellect in promoting individual and societal well-being from an Islamic worldview perspective.